Model Matematis untuk Multi-product Multi-warehouse Inventory Routing Problem - Giovano Alberto (Jurnal Rekayasa Sistem Industri, 2023)
Every business always aims to make significant profits. The corporation can cut expenses in one way or another. Logistics is one of the most expensive operations, and two-thirds of its expenditures are related to inventory and transportation. Inventory and transportation challenges must be addressed simultaneously in the supply chain to achieve the best results.This problem is modeled in the inventory routing problem (IRP). The development of the IRP model still has gaps with real conditions. The IRP model designed has not yet discussed the Multi-product Multi-warehouse Inventory Routing Problem (MMIRP) model. MMIRP takes into account the conditions of the types of goods that need to be sent, which vary and there are several warehouses that have goods of different types in one period of time. The results obtained after completing the model are the number of vehicles used, the number of goods of each type shipped, the travel routes generated by each vehicle, and the large costs generated based on the route design and inventory at each location.